Exploring The Service Quality's Impact on Repurchase Intention in Service Courier Customers - Aninda, Zahra Nur; Roosdhani, Mohamad Rifqy (Soegijapranata Catholic University, 2024)
The aim of this study was to verify the Service Quality impacts the intention of customers to Repurchase Intention directly and also through Customer Satisfaction and Customer Trust. The participants of this study comprised 162 JNT customers who were selected using a purposive sampling approach. The data underwent analysis using the SEM method with smart-PLS version 4.0. The examination employed various methods such as outer model test, inner model test, mediation test, and hypothesis testing. The validity test showed that values greater than 0.7 for the loading factor and values greater than 0.5 for the average variance extracted (AVE) were considered valid. The reliability test results showed that the instrument used was reliable because the composite reliability and Cronbach's alpha had a value greater than 0.7. The obtaining indicated that the impact of Service Quality on Repurchase Intention was both negative and not significant. In the mediation test, it was found that impact of Service Quality on customer satisfaction and customer trust was both positive. In addition, the impact of customer satisfaction and customer trust on repurchase intention was both positive and significant. Meanwhile, service quality had a negative and insignificant effect on repurchase intention.